Reliable Power System Operation Plan: Steady State Contingency Analysis - Hui Hwang, Goh (International Journal of Integrated Engineering, 2017)
Steady state contingency analysis focuses at the evaluation of the risk certain contingency possibly causes to an electrical network. This analysis is used to review the outage of elements such as transmission lines, transformers and generators, and investigation of the resulting effects on line power flows and bus voltages in Sabah, Malaysia grid transmission system. This is an extremely significant duty for network operators since network stability issues become essentially critical in electricity deregulation. In this paper, the analysis is performed to ensure the system meets grid code standards during normal operations and variety of contingencies condition. Therefore, this paper intended to put forward issues and recommendations towards attaining a steady power system operation plan. Steady state contingency analysis is to calculate power flows in outage states in which one or more system components are out of service. A transmission system must satisfy security criteria in both normal and outage states. This paper presented the steady state contingency analysis for the period of year 2015. The contingency analysis are performed by using the Siemens PTI software, Power System Simulator for Engineering (PSS/E).